Digestible tryptophan-to-digestible lysine ratio in diets for laying hens of 42 to 58 weeks of age - CALDERANO,Arele Arlindo (2016)
SUMMARY To determine the ideal digestible tryptophan-to-digestible lysine ratio in diets for laying hens of 42 to 58 weeks of age, 240 Hy-Line W-36 hens at 42 weeks of age were distributed in a completely randomized design with five treatments, eight replicates and six birds per experimental unit. At 42 weeks of age, the birds were subjected to experimental treatments that consisted of diets with equal amounts of nutrients, except for the digestible tryptophan level. The digestible tryptophan levels in the experimental diets were 0.149, 0.160, 0.171, 0.182 and 0.193%, generating digestible tryptophan-to-digestible lysine ratios of 21.5, 23.1, 24.6, 26.2 and 27.8%. The digestible lysine level in the diets was sub-optimal (0.694%). The same ratios between lysine and the other amino acids were maintained in all experimental diets. The ideal digestible tryptophan-to-digestible lysine ratio was estimated through the studied parameters using analysis of variance and polynomial regression analysis (α = 0.05). The digestible tryptophan-to-digestible lysine ratio in diets quadratically affected egg production, egg mass, feed conversion per egg mass and use efficiency of digestible lysine for egg mass. However, there were no effect (P>0.05) on egg weight, feed conversion per dozen eggs, use efficiency of digestible lysine for number of eggs produced, percentage of egg components and weight gain. The digestible tryptophan-to-digestible lysine ratio estimated for theses parameters ranged from 23.6 to 24.3%. The digestible tryptophan-to-digestible lysine ratio recommended in diets for laying hens of 42 to 58 weeks of age is 24.3%.